Histological changes in pulp-dentin complex in tooth subjected to traumatic occlusion and subluxation - Amaral, Marina Fuzette [UNESP]; Casatti, Cláudio Aparecido [UNESP]; Naqvi, Afsar Raza; Debortoli, Caio Vinicius Lourenço [UNESP]; Atili Brandini, Daniela [UNESP] (Springer Nature, 2024)
Background: This study evaluated the influence of traumatic occlusion in the dentin-pulp complex a molar teeth submitted to subluxation. Material and methods: Ninety Wistar rats were divided into groups Naïve (N), Subluxation (S) and Subluxation with traumatic occlusion (STO) and submitted to histological analysis after 7 and 21 days. A quantitative analysis was submitted to one-way ANOVA and Tukey's post-hoc test, and Chi-square and Bonferronís post-hoc test. Results: S and STO showed a significant increase in blood vessels area (p < 0.0005), amorphous fundamental substance (p < 0.0005) and reactionary dentin formation (p < 0.0005), as well as a decrease in the nuclear profile (p < 0.0005), odontoblast layer (p = 0.013 and p < 0.0005) by day 7 when compared with N. These changes normalized by day 21, except for the reactionary dentin (p < 0.0005) in both S and STO groups. Interestingly, the STO group exhibited significant changes in the increase of pulp calcification (p < 0.0005), presence of tubules with nuclei (p < 0.0005), and inflammatory infiltrate (p < 0.0005), as well reduction of nuclear profile (p < 0.0005), odontoblast layer (p < 0.0005) compared with N and S at day 21. Conclusions: STO impaired the defence response and decreased pulp regeneration capacity by increasing the inflammatory infiltrate and pulp calcification, and decreasing the nucleated cell number in the odontoblast layer and central pulp.
Keywords: Dental pulp; Rats; Traumatic dental occlusion; Wounds and Injuries